Monte Carlo calculation of buildup factors for 50 keV–15 MeV photons in tungsten up to 15 mean free paths. (May 2022) - Sardari, Dariush; Baradaran, Samaneh; Mofrad, Farshid Babapour; Marzban, Nazanin
Abstract: Exposure buildup factor values of tungsten for a point isotropic source in energy range 0.05–15 MeV up to 15 mfp are computed using Monte Carlo N-Particle code. Buildup factors of this study and ANSI/ANS-6.4.3 at some selected energies and penetration depths are compared. Highest discrepancies are observed for high-energy and/or high penetration depths. Highest error occurs at 15 MeV, amounting to 32%. In the energy range 2–6 MeV, our results show smaller values for all penetration depths and vice versa at higher energies. Highlights: Photon buildup factors for elemental (pure) tungsten are computed using MCNP. Photon energy from 50 keV to 15 MeV is considered. Photon penetration depths up to 15 mfp are examined. The agreement with ANSI is excellent up to 10 MeV and 10 mfp.